LncRNA HOTAIR promotes aerobic glycolysis by recruiting Lin28 to induce inflammation and apoptosis in acute lung injury - Junjie Xie; Zhicong Zheng; Bin Wang; Jianfang Zhang; Junqi Jiang; Fengde Wu; Xiangming Zhong; Jianfeng Chen (RNA Biology)
Acute lung injury (ALI) is a life-threatening condition with high rates of morbidity and mortality. Recently, there has been growing evidence suggesting a link between lncRNA HOTAIR and ALI. Nonetheless, the precise role and mechanism of lncRNA HOTAIR in ALI remain to be fully elucidated. siHOTAIR transfection, qPCR detection (HOTAIR), ELISA (TNF-α, IL-6, and IL-1β), Lactate detection, Glucose uptake experiment, Cell Apoptosis Analysis, Fluorescence in situ hybridization (FISH) assay. Through siHOTAIR transfection, we discovered that HOTAIR plays a role in the secretion of inflammatory factors in ALI and further regulates glucose uptake and metabolism in lung epithelial cells. Moreover, a comparison between HOTAIR knockdown cells and HOTAIR overexpression cells revealed that HOTAIR promotes cellular aerobic sugar metabolism, leading to increased secretion of inflammatory factors and cell apoptosis. Our in-depth research also identified an interaction between HOTAIR and the LIN28 protein. Knocking down HOTAIR resulted in the downregulation of LIN28 protein expression, which subsequently inhibited the expression of the glucose transporter GLUT1. This indicates that HOTAIR facilitates glucose uptake and boosts cellular aerobic glycolysis by modulating the LIN28 protein, thereby promoting inflammation and apoptosis in acute lung injury. The research findings presented in this article offer significant insights into the function of HOTAIR in ALI and suggest a potential therapeutic target for the treatment of this condition.